Influence of Risk Response Strategies on Construction Project Performance: Evidence from Embu County, Kenya - Brian Hamisi Kitsao; Boniface Wambua Mbuvi; Ajai Prakash (International Journal of Economics, Business and Innovation Research, 2026)
Risk response strategies have become very crucial in the performance and success of any construction project. Construction is a very key sector in Kenya. The sector accounts for about 7% of the Gross Domestic Product (GDP) of Kenya and employs about 1.5 million workers annually. Performance of the sector in Embu County and the country as a whole has been very poor with more than 70% of the constructions undertakings being delayed in one way or the other thus the need to examine the risk control strategies practiced in construction undertakings. The study mainly aimed at analyzing the impact of risk control strategies on the performance of construction projects within Embu County in Kenya. The research design used was Descriptive. The study sample included 288 construction staff from 204 construction sites. A questionnaire was employed as a tool for data collection. Analysis of data was done by means and standard deviation. Meanwhile the analysis done on the relation between the projects’ outcomes and the predictor variables involved multiple regression analysis. Correlation analysis’ findings indicated that risk response showed a statistically significant and a positive correlation to construction projects’ performance(r=0.767, p=0.001<0.05). Regression analysis further showed risk response had a strong, significant and positive impact in predicting performance of construction projects (β = 0.212 p=0.001 < 0.05). The study provides a geographically specific knowledge and situates the findings on a unique context of Embu County – Kenya - thereby filling the gap between international theories of risk management and local realities of a project in the sub-Saharan Africa.